The Structure and Function of Healing And Charm Spells - Andri Asmara; Yessi Fitriani; Arif Ardiansyah (Jadila: Journal of Development and Innovation in Language and Literature Education, 2020)
This study aimed to determine the structure and function of healing and charm spells in Makarti Jaya village, Banyuasin District. This research used a qualitative descriptive method. The source of the data was 22 healing and charm spells which are taken from three informants. The data analysis used was content analysis. The results of this study indicated that not all spells mention a name component because some spells do not have a name element but still do not reduce the magical value of the spell, for a name is not a measure of whether the spell is effective. In the component of the opening greeting, The suggestions received in the analyzed spell are aimed at making the spell look pleasing. In the objective component, all spells have the same goal, which is to captivate the opposite sex. Whereas the closing element of all spells uses words from Arabic such as laillahailallah muhamadarasulullah. From the analysis of the seven healing spells and fifteen charm spells, it showed that the spell has a different structure and function according to the verse contained in the spell.